Effects of Backslopping on Yeast Diversity and the Volatile Profile of Tarhana - Ozel, Burcu; Agirman, Bilal; Simsek, Omer; Erten, Huseyin (WILEY, 2025)
The primary challenge in tarhana production is the occurrence of spontaneous fermentation, which leads to non-standardized products. Thus, we investigated the effects of backslopping, a traditional method for inoculating fermented foods, on the yeast and volatile aroma compound diversity of tarhana dough. Backslopping fermentations were conducted at different temperatures (25 degrees C and 30 degrees C), pHs (3.70 and 4.00), and inoculation rates (5%, 10%, and 15%). The results revealed that the fermentation temperature and pH significantly influenced the diversity of yeast species and the volatile compound profile of the tarhana dough. However, despite some variations in the PCR-DGGE profiles, the metagenomic analysis revealed that the inoculation rate had minimal effect on yeast diversity, with species diversity remaining relatively constant over the cycles. Kazachstania humilis, Kazachstania bulderi, and Pichia kluyveri were the most prevalent yeast species across all experimental conditions. Pichia membranifaciens was exclusively detected in doughs fermented at 25 degrees C and pH 4.00, whereas Saccharomyces cerevisiae was observed only in doughs fermented at 30 degrees C. Tarhana doughs had a wide range of volatile compounds, the most abundant of which were terpenes and terpenoids, followed by esters, alcohols, aldehydes, and phenols. Doughs fermented at 25 degrees C and pH 3.70 were differentiated from other groups, particularly for their content of esters (e.g., ethyl acetate, ethyl lactate, ethyl decanoate, and ethyl octanoate) and alcohols (e.g., ethyl alcohol, isobutyl alcohol, benzyl alcohol). This study highlights the direct influence of backslopping on yeast diversity and its indirect impact on the aroma profile of tarhana dough, providing insights into the optimization of fermentation conditions for improved product standardization.
Keywords: backslopping; tarhana fermentation; volatile aroma compounds; yeast diversity; LACTIC-ACID BACTERIA; SACCHAROMYCES-CEREVISIAE; SOURDOUGH FERMENTATIONS; POPULATION-DYNAMICS; MICROBIAL ECOLOGY; NITROGEN; WHEAT; METABOLISM; PARAMETERS; STABILITY; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Microbiology; Mycology